Selective attention to the chemosensory modality. - Spence, C; Kettenmann, B; Kobal, G; McGlone, F (2000)
Previous studies have shown that behavioral responses to auditory, visual, and tactile stimuli are modulated by expectancies regarding the likely modality of an upcoming stimulus (see Spence and Driver, 1997). In the present study, we investigated whether people can also selectively attend to the chemosensory modality (involving responses to olfactory, chemical, and painful stimuli). Participants made speeded spatial discrimination responses (left vs. right) to an unpredictable sequence of odor and tactile targets. Odor stimuli were presented to either the left or the right nostril, embedded in a birhinally applied constant airstream. Tactile stimuli were presented to the left or the right hand. On each trial, a symbolic visual cue predicted the likely modality for the upcoming target (the cue was a valid predictor of the target modality on the majority of trials). Response latencies were faster when targets were presented in the expected modality than when they were presented in the unexpected modality, showing for the first time that behavioral responses to chemosensory stimuli can be modulated by selective attention.